Chironomidae Morphological Types and Functional Feeding Groups as a Habitat Complexity Vestige - Antczak-Orlewska, Olga; Płóciennik, Mateusz; Sobczyk, Robert; Okupny, Daniel; Stachowicz-Rybka, Renata; Rzodkiewicz, Monika; Siciński, Jacek; Mroczkowska, Agnieszka; Krąpiec, Marek; Słowiński, Michał; Kittel, Piotr (Frontiers in Ecology and Evolution, 2021)
Chironomid (Diptera: Chironomidae) larvae play an important role in a wide range of aquatic ecosystems. The study focuses on Chironomidae trophic guilds and morphological types as indicator traits in reconstructions of habitat changes in shallow water bodies. Mentum and ventromental plates are important mouthparts whose shape depends on food type and feeding behaviour. Chironomidae larvae strongly vary in the mode of life and feeding habits, representing almost every feeding group. Here we classified the mentum types into 16 groups and tested if they indicated similar past habitat changes as the Chironomidae functional feeding groups (FFGs), and tribes/subfamilies. Palaeoecological data of biotic and abiotic proxies were derived from short sequences from a Late Glacial oxbow and a nearby medieval moat located in Central Poland. The study revealed that the habitat substratum structure, vegetation and physicochemical conditions are associated both with the feeding types and morphological traits. This provides a valuable tool for future reconstructions of habitat changes.